Study on mechanical behaviors of buried FRP pipeline under geological sedimentation - Xiaoying ZHANG; Xiaohong MA; Cong WANG; Zhenlin LI; Hang ZHANG; Shaohua DONG (You-qi chuyun)
Objective Compared to conventional metal pipelines, fiber-reinforced plastic (FRP) pipelines demonstrate superior strength and lightweight properties. They have been progressively integrated into the station gathering and transmission segment within oil and gas fields. Among the prevalent geological hazards encountered by buried pipelines, geological sedimentation presents a substantial threat to the safe operation of buried FRP pipelines. Hence, assessing the mechanical behavior variations of FRP pipelines under geological sedimentation and the pertinent influencing factors are crucial for providing theoretical guidance to ensure their safe operation. Methods A buried FRP pipeline model was established, utilizing the finite element software ABAQUS, and taking into account the multi-layer nonlinear anisotropy of FRP pipelines. Hashin's failure criteria were employed to explore the maximum distribution of the compression and tension initiation criteria for both the FRP pipeline matrix and fiber at varying winding angles, settlements, and soil conditions. Results Under geological sedimentation, it was observed that the maximum values in the compression and tension initiation criteria for the matrix were higher compared to those of the fiber. This disparity results in larger impacts from matrix failure on the overall performance of pipelines. Across different lay-up winding angles, the lowest pipeline failure coefficient occurred at the interlayer angle of ±30°, creating favorable conditions for the safe operation of pipelines. The peak values of various failure coefficients were primarily concentrated near the middle of the settlement transition zone and at the boundary between the transition and settlement zones. Notably, alterations in soil conditions were found to exert the most significant influence on the failure coefficient of the pipeline intermediate layers. Conclusion The ABAQUS composite layup module has proven effective in simulating the characteristics of FRP composite pipes. The simulation outcomes provide a theoretical foundation for choosing an appropriate layup winding type and conducting safety analysis for FRP pipelines under geological settlement conditions.